Khronika natsional'noi politiki . Khronika natsional'noi politiki . Chronicle of National Politics . Хроника национальной политики - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on the research conference devoted to the 50th anniversary of the deportation of Russian minorities to Siberia. Передача о научно-практической конференции, посвященной 50-летию депортации малых народов России в Сибирь.